2020
DOI: 10.1109/jstars.2020.3001022
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Stitching for Hyperspectral Images Using Robust Feature Matching and Elastic Warp

Abstract: Hyperspectral images, which contain not only spatial information but also rich spectral information, have been extensively applied to the fields of agriculture, urban planning and so on. However, it is difficult for a single image to cover a large area. Therefore, it requires to take photos of various parts and apply image stitching technology to obtain a panoramic hyperspectral image. When the viewpoint of the scene changes a lot, the ghost issue will occur with traditional methods. In order to get the high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…From the analysis in Figure 8, it can be concluded that as the number of tasks increases, the success rate of the two Ours Literature [15] Literature [11] Literature [12] 6 Complexity algorithms decreases. As the task is successfully executed, the energy of mobile resources is consumed.…”
Section: Task Scheduling Of Grid Resourcesmentioning
confidence: 96%
See 2 more Smart Citations
“…From the analysis in Figure 8, it can be concluded that as the number of tasks increases, the success rate of the two Ours Literature [15] Literature [11] Literature [12] 6 Complexity algorithms decreases. As the task is successfully executed, the energy of mobile resources is consumed.…”
Section: Task Scheduling Of Grid Resourcesmentioning
confidence: 96%
“…Regarding the algorithm research on service matching, the most influential one is the elastic matching algorithm [15]. e algorithm mainly considers service matching based on functionality, that is, considering the input and output parameters of the matching service.…”
Section: Related Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, image stitching algorithms are not able to perform datacube stitching. Only Zhang [18] proposed a robust elastic warp that fits first to the central spectral plane from one cube to another and then adapts the transformation to other spectral planes.…”
Section: Improved Warping Methodsmentioning
confidence: 99%
“…Then, reference layer stitching is performed by finding a single adequate model between the reference layer from datacube 1 and datacube 2. The same model is applied to other layers since each datacube is already aligned within layers [18].…”
Section: Related Workmentioning
confidence: 99%